Crack tip monitoring by multiscale optical experimental techniques. (February 2022) - Farahani, Behzad V.; Direito, Frederico; Sousa, Pedro J.; Tavares, Paulo J.; Infante, Virginia; Moreira, Pedro P.M.G.
Highlights: A crack tip monitoring is studied through multiscale contactless optical methods. DIC and ESPI techniques are employed to measure the experimental data. The crack is detected and its length is measured by both methods. SIF is calculated and compared to the reference solution. The crack opening evolution is studied by ESPI and DIC analyses. Abstract: This study focuses on the development of a complementary fatigue crack-tip evaluation approach with multiscale optical techniques with different resolutions. A middle tension (MT) specimen, of aluminium alloy AA6082-T6, was prepared and submitted to a cyclic fatigue loading to generate a fatigue crack. Then, it was statically loaded under a uniaxial tensile condition, and two non-contact full-field optical techniques, Digital Image Correlation (DIC) and Electronic Speckle Pattern Interferometry (ESPI), were employed to acquire the experimental data. While the specimen is loaded with incremental force values, the behaviour of the cracked area is monitored, with displacement and deformation fields acquired for each force increment. The obtained data is thereby used to calculate the Stress Intensity Factor (SIF) and monitor the crack opening evolution. An overdeterministic algorithm was developed for the SIF determination. The main contribution of the present work is the development of a complementary multiscale methodology, which employs available techniques with different resolutions to monitor the tip of a fatigue crack, drawing a comparison between calculated parameters for each system to shift from one technique to the higher resolution one and validating the proposed methodologies. The obtained SIF values are compared to the reference solution proposed by ASTM E647, and an acceptable agreement has been verified amongst the results.